Eksplorasi Media Sosial: Mengungkap Mata Pisau Jalan Pintas Menuju Keadilan dalam Birometri Hukum - Bawi, Allowisius; Atek, Liboria G.; Kelanit, Mauritius; S, Lestari Wulandari (Universitas Ekasakti, 2023)
In the ever-evolving digital era, the presence of social media has significantly impacted legal systems and the enforcement of justice. This article delves into a thorough exploration of the role of social media as a shortcut tool that can reveal gaps in the bureaucracy of law enforcement. The focus is on the concept of the